Atlas of perfumed botany - Ellena, Jean-Claude; Doering-Froger, Karin; Butler, Erik, 1971- (Cambridge, Massachusetts : The MIT Press, 2022)
"A lavishly illustrated cartography of fragrance that charts the botany and geography of perfume composition"--
Woods and barks -- Leaves -- Flowers -- Fruits -- Gums and resins -- Seeds -- Roots.
Includes bibliographical references (page 165).
in English.
Keywords: Botany; Aromatic plants -- Utilization